2017
DOI: 10.1186/s12885-017-3307-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lymphovascular invasion on lymph node metastasis for patients undergoing radical prostatectomy with negative resection margin

Abstract: BackgroundThe association between lymphovascular invasion and lymphatic or hematogenous metastasis has been suspected, with conflicting evidence. We have investigated the association between the risk of biochemical recurrence and lymphovascular invasion in resection margin negative patients, as well as its association with lymph node metastasis.MethodsOne thousand six hundred thirty four patients who underwent radical prostatectomy from 2005 to 2014 were selected. Patients with bone or distant organ metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
2
11
0
Order By: Relevance
“…Lymphovascular invasion (LVI) is a common histopathological finding in malignant tumors, including CRC. LVI is characterized by the ability of malignant cells to detach from the primary tumor mass and then penetrate the lymphatic or other vascular channels [20,21]. Therefore, the addition of the assessment of LVI to the current TNM staging system may be a more accurate indicator of patient prognosis in stage III CRC, which may allow planning for more effective use of adjuvant therapy and patient follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphovascular invasion (LVI) is a common histopathological finding in malignant tumors, including CRC. LVI is characterized by the ability of malignant cells to detach from the primary tumor mass and then penetrate the lymphatic or other vascular channels [20,21]. Therefore, the addition of the assessment of LVI to the current TNM staging system may be a more accurate indicator of patient prognosis in stage III CRC, which may allow planning for more effective use of adjuvant therapy and patient follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphovascular invasion, also known as minimal lymphatic involvement, has been frequently reported as a prognostic factor to predict biochemical recurrence (BCR) after radiotherapy and radical prostatectomy [36][37][38][39]. In the cause analysis of BCR, the increasing risk was mainly from progression to lymph node metastasis instead of residual tumor cells of positive surgical margins [39]. A recent study reported that the lymphovascular invasion of PCa cells has a significantly prognostic impact on disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…88,89 This has been confirmed in several large (number of cases ranging from 742 to 6678) contemporary series based on examination of the hematoxylin-and-eosin-stained slides. 76,[90][91][92][93][94] In these series lymphovascular invasion was identified in 2.8-21.5% of specimens (median, 7.4%). In all six large contemporary series, the presence of lymphovascular invasion was an independent predictor of biochemical recurrence on multivariable analysis.…”
Section: Dj Grignonmentioning
confidence: 72%